2017
DOI: 10.1556/0406.18.2017.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a single aerobic exercise session on body image

Abstract: Background and Objectives: Most research on the effects of exercise on body image has concentrated on the benefits of regular exercise. However, some research has indicated that exercise has an immediate impact on body image. The aims of this study were to investigate the immediate effects of aerobic exercise in a fitness class and the at-home environment on body image, and to examine the impact of nutritional status (i.e., normal weight vs. overweight/obesity) and exercise addiction on these changes. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Further factors also include sex, age, mean and the relationship of the body with cognitive processes such as cultural and social beliefs, values and attitudes (Rica et al, 2018a;Gardner, 2011). In relationship to body image and exercise, studies have shown improvement on body image after acute (Béres, Czeglédi & Babusa, 2017;Carraro, Nart & Scarpa, 2010) and chronic (Baştuğ et al, 2016;Vocks et al, 2009) protocols. However, no significant differences were found in our study after a single session of HIIT body work.…”
Section: Discussionmentioning
confidence: 99%
“…Further factors also include sex, age, mean and the relationship of the body with cognitive processes such as cultural and social beliefs, values and attitudes (Rica et al, 2018a;Gardner, 2011). In relationship to body image and exercise, studies have shown improvement on body image after acute (Béres, Czeglédi & Babusa, 2017;Carraro, Nart & Scarpa, 2010) and chronic (Baştuğ et al, 2016;Vocks et al, 2009) protocols. However, no significant differences were found in our study after a single session of HIIT body work.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that women in both groups showed a moderate improvement in body appreciation following the one-hour exercise session. Further, no significant differences in body appreciation were found between the two groups (Béres et al, 2017). These two studies provide preliminary evidence for the positive association between exercise and positive body image.…”
Section: Exercise-based Positive Body Image Enhancementmentioning
confidence: 55%
“…At least two quantitative studies have specifically looked at the association between exercise and positive body image (Béres, Czeglédi, & Babusa, 2017;Homan & Tylka, 2014). The first study found that college-aged women (N = 321) who frequently engaged in moderate exercise also reported greater body appreciation, internal body orientation, and body functionality satisfaction.…”
Section: Exercise-based Positive Body Image Enhancementmentioning
confidence: 99%
“…The study conducted by Béres, Czeglédi and Babusa (2017) shows that even a single aerobic session has a positive effect on the body image in Hungarian women.…”
Section: Resultsmentioning
confidence: 98%